Tradeoffs between equality and difference: Immigrant integration, multiculturalism, and the welfare state in cross-national perspective - Ruud Koopmans (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
This paper investigates how integration policies and welfare state regimes have affected the socio-economic integration of immigrants, focusing on eight European countries: Germany, France, the United Kingdom, the Netherlands, Switzerland, Sweden, Austria, and Belgium. It presents comparative data on integration policies and welfare states regimes. The expectations derived from this comparative policy analysis are tested with cross-national data on integration outcomes regarding labour market participation, spatial segregation, and incarceration. The results suggest that multicultural policies, which grant immigrants easy access to equal rights and do not provide strong incentives for host country language acquisition and interethnic contacts, when combined with a generous welfare state, have produced low levels of labour market participation, high levels of segregation, and a strong overrepresentation of immigrants among those convicted for criminal behaviour. Sweden, Belgium, and the Netherlands, which have combined multicultural policies with a strong welfare state, display relatively poor integration outcomes. Countries that either had more restrictive or assimilationist integration policies (Germany, Austria, Switzerland, France) or a relatively lean welfare state (the United Kingdom) have achieved better integration results. These differences are highly consistent across the three domains of integration that are examined, with the exception of segregation rates in the United Kingdom. – – Das vorliegende Papier untersucht, wie sich integrationspolitische Ansätze und wohlfahrtsstaatliche Regime auf die Integration von Migranten auswirken. Es werden vergleichende Daten zu den Integrationspolitiken und wohlfahrtsstaatlichen Regimen in acht europäischen Ländern vorgestellt: Deutschland, Frankreich, Großbritannien, Niederlande, Schweiz, Schweden, Österreich und Belgien. Die daraus abgeleiteten Hypothesen werden mit ländervergleichenden Daten zu den Integrationsergebnissen in den Bereichen Arbeitsmarktbeteiligung, Segregation der Wohnbevölkerung und Inhaftierung überprüft. Die Ergebnisse deuten darauf hin, dass multikulturelle Politikansätze, die Migranten einen leichten Zugang zu gleichen Rechten gewähren und keine starken Anreize setzen, die Sprache des Aufnahmelandes zu erlernen und interethnische Kontakte zu pflegen, in der Kombination mit großzügigen wohlfahrtsstaatlichen Leistungen zu einer geringen Erwerbsbeteiligung, starker Segregation und einer deutlichen Überrepräsentation von Immigranten unter Strafgefangenen führen. Schweden, Belgien und die Niederlande, die multikulturelle Politik mit einem starken Wohlfahrtsstaat verbunden haben, verzeichnen relativ schwache Integrationserfolge. Länder mit entweder restriktiverer bzw. stärker auf Assimilation ausgerichteter Integrationspolitik (Deutschland, Österreich, die Schweiz, Frankreich) oder einem eher schlanken Wohlfahrtsstaat (Großbritannien) haben bessere Integrationsergebnisse erreicht. Die Unterschiede sind über die drei untersuchten Integrationsbereiche hinweg sehr konsistent, mit Ausnahme des Segregationsniveaus in Großbritannien.
Keywords: 300